The relationship between discharge medications and falls in post‐hospitalised older adults: A 6‐month follow‐up. (25th February 2019) - Lam, Kenneth; Lee, Den‐Ching A.; Lalor, Aislinn F.; Stolwyk, Rene; Russell, Grant; Brown, Ted; McDermott, Fiona; Haines, Terry P.
Abstract : Objective: To identify discharge medications, especially psychotropic medications that are associated with falls, amongst older adults within 6 months following hospitalisation. Methods: Negative binomial regression was used to examine relationships between discharge medications and falls in older post‐hospitalised adults. Multiple regression that considered falls risk factors at discharge was performed. Results: Data for 267 participants showed that discharge medications were not independently associated with falls postdischarge after adjustment for other falls risk factors. Male gender (adjusted incidence rate ratio [95% confidence interval, CI]) 2.15 [1.36‐3.40]), higher depression scores (1.14 [1.05‐1.25]) and co‐morbidity of neurological disease other than stroke (5.98 [3.08‐11.60]) were independently associated with an increased rate of falls. Higher depression scores (1.20 [1.11‐1.31]) and co‐morbidity of cancer (1.97 [1.20‐3.25]) were independently associated with an increased rate of injurious falls in the 6 months postdischarge. Conclusion: Falls prevention strategies, other than hospital discharge medication management in the postdischarge older adults, warrant investigation.